Stanislavsky: Uncensored and Unabridged (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The paper traces a historical and biographical panorama of Konstantin Stanislavsky's last decades of life to understand to what extent his image and work were framed, manipulated, and even modified, inside and outside Russia. Professor Sharon Marie Carnicke recalls the complexities and contradictions to which Stanislavsky was subordinated both in Russia in the face of Stalin's censorship and materialistic-dialectic propaganda and in the US, either through the tours of the Moscow Art Theater that boosted the director in the West, or through the crucial copyright contract signed with his translator Elizabeth Hapgood.
Keywords: Konstantin Stanislavsky; Publishing process; Theater History